2021
DOI: 10.1038/s41434-021-00227-z
|View full text |Cite
|
Sign up to set email alerts
|

Human MiniPromoters for ocular-rAAV expression in ON bipolar, cone, corneal, endothelial, Müller glial, and PAX6 cells

Abstract: Small and cell-type restricted promoters are important tools for basic and preclinical research, and clinical delivery of gene therapies. In clinical gene therapy, ophthalmic trials have been leading the field, with over 50% of ocular clinical trials using promoters that restrict expression based on cell type. Here, 19 human DNA MiniPromoters were bioinformatically designed for rAAV, tested by neonatal intravenous delivery in mouse, and successful MiniPromoters went on to be tested by intravitreal, subretinal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 115 publications
(164 reference statements)
0
18
0
Order By: Relevance
“…The rAAV genome plasmid (pEMS2143) used here has also been used previously 56 , 57 and is available from Addgene ( www.addgene.org ). In brief, it is ssAAV-smCBA-EmGFP-WPRE, where ssAAV is single-stranded AAV, smCBA is a smCBA enhancer chosen for ubiquitous expression, 25 , 56 , 57 , 58 EmGFP is used, 59 and WPRE is the 3′ UTR woodchuck hepatitis virus post-transcriptional regulatory element mut6. 60 , 61 For this work, pEMS2143 was packaged into either rAAV9 or PHP.B by the University of Pennsylvania Vector Core (Philadelphia, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The rAAV genome plasmid (pEMS2143) used here has also been used previously 56 , 57 and is available from Addgene ( www.addgene.org ). In brief, it is ssAAV-smCBA-EmGFP-WPRE, where ssAAV is single-stranded AAV, smCBA is a smCBA enhancer chosen for ubiquitous expression, 25 , 56 , 57 , 58 EmGFP is used, 59 and WPRE is the 3′ UTR woodchuck hepatitis virus post-transcriptional regulatory element mut6. 60 , 61 For this work, pEMS2143 was packaged into either rAAV9 or PHP.B by the University of Pennsylvania Vector Core (Philadelphia, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Given the demonstrated differences in other promoters specificity in degenerate retinas 61 and when moving to primates, 60 L7-6 appears to be particularly attractive and adds to a growing armory of retinal-cell-population-specific mini-promoters. 30 , 73 , 74 , 75 , 76 , 77 …”
Section: Discussionmentioning
confidence: 99%
“…Since AAV vectors currently represent the least toxic and most effective method of gene delivery in vivo , this poses important challenges for future research into cell-based therapies. While several studies have reported Müller glia-specific AAV-based minipromoter constructs derived from genes other than GFAP ( Korecki et al, 2021 ; Lin et al, 2022 ), these too may show ectopic expression when used to overexpress specific genes. In mice, where transgenic reagents such as the GlastCreERT2;Sun1-GFP that can reliably and irreversibly label glia are readily available, prospective genetic lineage analysis should be performed routinely in conjunction with AAV-based manipulations.…”
Section: Discussionmentioning
confidence: 99%